The American Bourgeoisie
IX, 284 p.
Keywords: This volume engages a fundamental disciplinary question about this period in American history: how did the bourgeoisie consolidate their power and fashion themselves not simply as economic leaders but as cultural innovators and arbiters? It also explains how culture helped Americans form both a sense of shared identity and a sense of difference.